2001
DOI: 10.1002/1522-2675(20011017)84:10<3178::aid-hlca3178>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantio- and Regioselective Allylic Alkylations Catalyzed by Chiral [Bis(dihydrooxazole)]molybdenum Complexes

Abstract: In memory of Luigi M. VenanziA series of chiral C 2 -symmetric bis[dihydrooxazoles] with a trans-1,2-diaminocyclohexane backbone was synthesized. In view of the promising results obtained by Trost et al. with related bis[pyridine] ligands, we tested these new ligands in the enantioselective molybdenum-catalyzed allylic alkylation of 1-and 3-monosubstituted allylic substrates. Enantiomer excesses of up to 98% and branched/linear ratios of up to 11 : 1 were obtained with (E)-3-(alkyl)allyl carbonates. (E)-3-Phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…Although the mode of coordination of 8 and 11 to Mo in the active catalyst has not been firmly established,10, 15, 16 there is a growing body of evidence that a tridentate, anionic, fac ‐binding mode is involved. By analogy, it can be argued that the R group in ligands 12 could act as an anchor, presumably occupying an “equatorial” position in the cyclic complex, thereby mimicking the rigid scaffold of 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mode of coordination of 8 and 11 to Mo in the active catalyst has not been firmly established,10, 15, 16 there is a growing body of evidence that a tridentate, anionic, fac ‐binding mode is involved. By analogy, it can be argued that the R group in ligands 12 could act as an anchor, presumably occupying an “equatorial” position in the cyclic complex, thereby mimicking the rigid scaffold of 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Trost originally proposed a bidentate coordination of ligand 8 to molybdenum with trans ‐configuration of the ligating nitrogens about the metal center ( A , see below) 10 Pfaltz has reported an X‐ray structure of the complex obtained from ligand 11 and [(EtCN) 3 Mo(CO) 3 ], which shows a tridentate coordination B (with two sp 2 nitrogens and one carbonyl group involved in the coordination) 16. Most recently, Krska, Hughes and Trost have reported on the X‐ray structure of the Mo–η 3 ‐complex C (Ar = Ph), in which the binding to the deprotonated amidic nitrogen has been confirmed by solution 15 N NMR spectroscopy 15.…”
Section: Resultsmentioning
confidence: 99%
“…After a brief survey of the literature, it was found that ethyl oxazoline-2-carboxylates 10 could be prepared in a single step starting from ethyl oxamate 9, following a procedure reported by Pfaltz and co-workers. 15 This involved an activation of the starting material by a triethyloxonium salt, followed by transamidation and ring closure. Thus, compounds 10a and 10b bearing a phenyl and a tert-butyl group, respectively, on the oxazoline ring were readily synthesized.…”
Section: Synthesis Of the Ligandsmentioning
confidence: 99%
“…These reactions may proceed by means of intermediates in which isomerization (K eq in Scheme 1) is slow relative to nucleophilic reaction. In contrast, Mo-based catalysis (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) proceeds with loss of substrate stereochemistry and provides the opportunity in reactions with asymmetric ligands to obtain high product ee, starting with either the linear substrate or racemic branched product (Scheme 1). These reactions proceed by a dynamic kinetic asymmetric transformation (40) with rapid equilibration of the two diastereomeric -allyl complexes before nucleophilic attack (Scheme 1).…”
mentioning
confidence: 93%